The ultrastructure of Upper Palaeozoic and Mesozoic pollen from southern Africa and Asia - Zavada, Michael S. (BERNARD PRICE INSTITUTE FOR PALAEONTOLOGICAL RESEARCH, 2004)
The dispersed pollen taxa Cycadopites, Monosulcites, Bennetitteaepollenites, Pityosporites, and Inaperturopollenites recovered from Permian to Jurassic sediments in southern Africa and Asia were examined ultrastructurally. Cycadopites, Monosulcites, Bennetitteaepollenites and Inaperturopollenites wall structure is characterized by homogeneous outer layer that is variously lacunate, and is underlain by a lamellated basal layer. Only one species of Monosulcites recovered from Jurassic sediments of Afghanistan showed a well-developed tectum, an infrastructural layer composed of columellae, or irregularly shaped columellae underlain by a basal layer. The saccate pollen of Pityosporites has an infrastructural layer of irregularly shaped anastomosing rods, the sacci are formed by an expansion of infrastructural layer in the region of the saccus (i.e. protosaccate sensu Scheuring). A majority of Permian, Triassic and Jurassic saccate and non-saccate monosulcate pollen is characterized by limited morphological diversity with regard to sculpturing and wall structure type compared to the diversity in angiosperm monosulcate pollen; however, there are pre-Cretaceous monosulcate pollen types that exhibit angiospermous pollen characteristics.